2011
DOI: 10.4028/www.scientific.net/amm.52-54.2116
|View full text |Cite
|
Sign up to set email alerts
|

Study of TiC Cutting Tool Insert Using Microwave Synthesis

Abstract: Microwave processing ceramics is emerging fast as a new field of ceramic processing and material synthesis. The past year has witnessed significant progress in the aspects of commercialization and application of the technology to new areas. Further research states that Titanium Carbide (TiC) is the best cutting tool due to its high melting point and by that reason this project aims to show the difference between conventional sintering, microwave sintering and Hot Isostatic Pressing (HIP). Two different composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…This is to ensure that the heating is uniform all around the insert. The small crucible was then placed inside a larger crucible with a diameter of 65 mm at the opening and submerged inside 50 cm 3 (~ 300 mesh) of Silicon Carbide (SiC) powder (Alfa Aesar) which functions as a susceptor to aid in rapid hybrid microwave heating (Fig. 1).…”
Section: B Sintering Processmentioning
confidence: 99%
See 1 more Smart Citation
“…This is to ensure that the heating is uniform all around the insert. The small crucible was then placed inside a larger crucible with a diameter of 65 mm at the opening and submerged inside 50 cm 3 (~ 300 mesh) of Silicon Carbide (SiC) powder (Alfa Aesar) which functions as a susceptor to aid in rapid hybrid microwave heating (Fig. 1).…”
Section: B Sintering Processmentioning
confidence: 99%
“…Charmond et al investigated on the densification and microstructure changes of 2 mol% yttria-stabilized zirconia nano powder and concluded that hybrid heating produced homogeneous microstructures whereas direct microwave heating led to rather heterogeneous microstructures due to thermal gradients [2]. Thauri et al analyzed on the mechanical properties of titanium carbide (TiC) in hybrid microwave sintering; and found out that samples with improved density and hardness were produced by hybrid microwave sintering in a shorter processing time which is 93% faster than conventional sintering and 50% faster than Hot Isostatic Pressing [3]. ITO ceramics generally are difficult to achieve full densities using conventional heating because of the volatilization property of both indium oxide (In2O3) and tin oxide (SnO2) at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…These heat treatments are basically performed in a traditional furnace through convection. Rapid heating using microwave energy on the other hand has shown to have significant improvements in the mechanical properties of ceramics, metals and alloys [1][2][3][4][5]. Microwave heating is completely different from the conventional heating method.…”
Section: Introductionmentioning
confidence: 99%